(untitled) (Journal of actual problems of jurisprudence, 2019)
This article discusses the main problem of the definition of subjective symptom computer crimes. Analyzes the norms of the Criminal Code of the Republic of Kazakhstan regulating the fight against computer crime, and suggests ways to improve these standards by specifying the subject of the crime. Keywords: computer crime, guilt, motive, purpose, network, Internet, computer information, illegal.